Environmental regulation in transition: Policy officials’ views of regulatory instruments and their mapping to environmental risks - Taylor, Christopher M.; Gallagher, Elaine; Pollard, Simon J. T.; Rocks, Sophie A.; Smith, Heather M.; Leinster, Paul; Angus, Andrew (Elsevier, 2018)
This study re-analysed 14 semi-structured interviews with policy officials from the UK Department for Environment, Food and Rural Affairs (Defra) to explore the use of a variety of regulatory instruments and different levels of risk across 14 policy domains and 18 separately named risks. Interviews took place within a policy environment of a better regulation agenda and of broader regulatory reform. Of 619 (n) coded references to 5 categories of regulatory instrument, ‘command and control’ regulation (n = 257) and support mechanisms (n = 118) dominated the discussions, with a preference for ‘command and control’ cited in 8 of the policy domains. A framing analysis revealed officials' views on instrument effectiveness, including for sub-categories of the 5 key instruments. Views were mixed, though notably positive for economic instruments including taxation, fiscal instruments and information provision. An overlap analysis explored officials' mapping of public environmental risks to instrument types suited to their management. While officials frequently cite risk concepts generally within discussions, the extent of overlap for risks of specific significance was low across all risks. Only ‘command and control’ was mapped to risks of moderate significance in likelihood and impact severity. These results show that policy makers still prefer ‘command and control’ approaches when a certainty of outcome is sought and that alternative means are sought for lower risk situations. The detailed reasons for selection, including the mapping of certain instruments to specific risk characteristics, is still developing.
Keywords: Risk; Regulation; Policy; Design; Environment; Instrument